2019
DOI: 10.1111/jcmm.14654
|View full text |Cite
|
Sign up to set email alerts
|

Testis developmental related gene 1 regulates the chemosensitivity of seminoma TCam‐2 cells to cisplatin via autophagy

Abstract: We previously identified testis developmental related gene 1 (TDRG1), a gene implicated in proliferation of TCam‐2 seminoma cells. Recent evidence has revealed that autophagy influences the chemosensitivity of cancer cells to chemotherapy. However, whether TDRG1 protein regulates autophagy in seminoma cells and influences their sensitivity to cis‐dichlorodiammine platinum (CDDP) remains unknown. In this study, we used TCam‐2 cells and male athymic BALB/c nude mice with xenografts of TCam‐2 cells to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 55 publications
(132 reference statements)
0
24
0
Order By: Relevance
“…12,13 Previously, we showed that sensitivity of seminoma to CDDP is regulated by testis development-related gene 1 (TDRG1), which acts as an oncogene in testis. [14][15][16] Furthermore, this effect of TDRG1 on CDDP chemosensitivity has been found to be regulated by lncRNA H19 and miRNA-106b-5p. 15 Of note, tumour cells are often versatile in response to host microenvironment changes, such as high treatment burden.…”
mentioning
confidence: 99%
“…12,13 Previously, we showed that sensitivity of seminoma to CDDP is regulated by testis development-related gene 1 (TDRG1), which acts as an oncogene in testis. [14][15][16] Furthermore, this effect of TDRG1 on CDDP chemosensitivity has been found to be regulated by lncRNA H19 and miRNA-106b-5p. 15 Of note, tumour cells are often versatile in response to host microenvironment changes, such as high treatment burden.…”
mentioning
confidence: 99%
“…Evidence is building on the contributory role of these mechanisms in several cancer models that acquire a resistance to cisplatin and deserve explorations in studies dedicated to TGCTs. Indeed, a recent study on TCam-2 cell lines (including an in vivo mouse model) showed that testis developmental related gene 1 ( TDRG1 ) promotes autophagy via the p110β/Rab5/Vps34 (PI3-kinase class III) cascade, contributing to cisplatin resistance [ 74 ]. Overall, and despite that specific studies for TGCTs are needed to confirm the relevance of these mechanisms, insights from other tumor models can be used as surrogates to pinpoint general mechanisms likely to be involved in cisplatin resistance ( Table S1 ).…”
Section: Dissecting Cisplatin Resistance Mechanismsmentioning
confidence: 99%
“…Cells was cultured in DMEM medium + 10% fetal bovine serum along with penicillin (100 U/ml) and streptomycin (100 μg/ml, Invitrogen, Carlsbad, CA) at 37˚C with 5% CO 2 . Although Eppelmann et al demonstrated that the TCam-2 cell line was heterogenous, the cell line is still considered as an optimum seminoma cell model and extensively used in relevant studies [16][17][18].…”
Section: Cell Line and Cell Culturementioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of endogenous small noncoding RNA molecules containing [18][19][20][21][22][23][24][25] nucleotides, which always function as post-transcriptional regulators of the mRNAs expression through binding to the 3′-untranslated region (3′-UTR) of their targets [8,9]. miRNAs have been found to be involved in a variety of biological processes, including tumor occurrence and progression [10,11].…”
Section: Introductionmentioning
confidence: 99%